2021
DOI: 10.3390/jof7020102
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Linkages among Fruiting Depth, Weight, and Maturity in Irrigated Truffle Fungi Marks the Complexity of Relationships among Morphogenetic Stages

Abstract: The highly prized black truffle (Tuber melanosporum) has become a model species for ectomycorrhizal fungi biology. However, several questions concerning its reproductive phase remain unanswered. To provide new hypotheses on the fruitbody formation process, we have explored the causal links among development characters of black truffle fruitbodies that are primarily linked to either the mating process, fruitbody growing stage, or maturation. Path analysis was applied to test causal models outlining the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…aestivum (Büntgen et al ., 2017) and T . melanosporum (Garcia‐Barreda et al ., 2021), which revealed the absence of a causal link between ascocarp ripeness and size. Indeed, small truffles can be ripe while large truffles can be immature (Büntgen et al ., 2017; Garcia‐Barreda et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…aestivum (Büntgen et al ., 2017) and T . melanosporum (Garcia‐Barreda et al ., 2021), which revealed the absence of a causal link between ascocarp ripeness and size. Indeed, small truffles can be ripe while large truffles can be immature (Büntgen et al ., 2017; Garcia‐Barreda et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, small truffles can be ripe while large truffles can be immature (Büntgen et al ., 2017; Garcia‐Barreda et al ., 2021). Moreover, there is no evidence that ascocarps must reach a minimum size to mature or that weight gain and ripeness evolve together (Garcia‐Barreda et al ., 2021). The absence of correlation between weight and maturity differentiates truffles from some epigeous fungi, for which species‐specific size‐ripeness associations are reported (Büntgen et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These molecules were previously found in T. melanosporum truffles [ 1 , 7 ]. Truffle maturity changes can be observed in the spore maturity [ 27 ], chemical composition [ 28 ], and bacterial community profile [ 29 , 30 ] throughout the season. As indicated by Caboni et al (2020) [ 31 ], metabolite levels in truffles strongly depend on the month of harvesting which is directly related to the maturity stage.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of our results with those from other Tuber species is problematic since most of them have much shorter growing seasons and likely only one life cycle. For example, Tuber melanosporum commonly, but not exclusively (Rebière, 1967), fruits in its Mediterranean habitats from the end of December until early March (Callot, 1999;Garcia-Barreda et al, 2021), and only small and unripe primordia between 0.5-1.0 mm have been described to form in summer and autumn (Pradel, 1914;Pacioni et al, 2014). It has been reported that several months are needed from the induction and initial production of primordia to fully mature Tuber melanosporum fruitbodies (Pacioni et al, 2014;Le Tacon et al, 2013;Garcia-Barreda et al, 2021).…”
Section: Truffle Characteristics and Locationsmentioning
confidence: 99%